Evidence mapping and meta-analysis of traditional Chinese medicine for postmenopausal osteoporosis - Xi Xi; Xue Yan; Jingchun Fan; Yanying Zhang; Zhandong Wang (Medicine, 2026)
Background: Postmenopausal osteoporosis (PMOP) is a common metabolic bone disorder characterized by estrogen deficiency – induced bone loss and increased fracture risk. Traditional Chinese medicine (TCM) has demonstrated unique advantages in PMOP management, but comprehensive, standardized evidence synthesis remains limited. Methods: Chinese and English databases (CNKI, Wanfang, VIP, SinoMed, PubMed, EMBASE, Web of Science, and Cochrane Library) were systematically searched up to July 31, 2024. Eligible studies included interventional, observational, and evidence-based research. Data extraction and quality assessment followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses 2020 statement. Meta-analyses were performed using RevMan 5.4 with random- or fixed-effects models depending on heterogeneity. Results: A total of 319 studies were included: 232 interventional, 60 observational, 25 systematic reviews or meta-analyses, and 2 guidelines. Among 99 randomized controlled trials, TCM interventions significantly improved clinical efficacy (risk ratio = 1.22, 95% confidence interval [CI]: 1.17–1.27, I 2 = 55%) and reduced pain (standardized mean difference [SMD] = −2.15, 95% CI: −2.95 to − 2.17, I 2 = 96%). TCM also enhanced bone mineral density at both lumbar (SMD = 0.74, 95% CI: 0.57–0.91, I 2 = 90%) and femoral sites (SMD = 0.60, 95% CI: 0.41–0.80, I 2 = 89%). Conclusion: TCM interventions significantly improve bone density and pain outcomes in PMOP. However, high heterogeneity and moderate methodological quality highlight the need for high-quality, standardized clinical trials integrating syndrome differentiation.